Preoperative Noninvasive Mapping Allowed Targeted Concomitant Surgical Ablation and Revealed COVID-19 Infection. (8th March 2021) - Mork, Constantin; Koechlin, Luca; Streif, Matthias; Hollinger, Alexa; Siegemund, Martin; Eckstein, Friedrich; Santer, David
Abstract : In March 2020, a 64-year-old female with mitral valve insufficiency and persistent atrial fibrillation underwent preoperative noninvasive mapping for developing an ablation strategy. In the computed tomography (CT) scan, typical signs of COVID-19 were described. Since the consecutive polymerase chain reaction (PCR) test was negative, the severely symptomatic patient was planned for urgent surgery. Noninvasive mapping showed that atrial fibrillation was maintained by left atrial structures and pulmonary veins only. On admission day, the preoperative routine COVID-19 PCR test was positive, and after recovery, uneventful mitral valve repair with cryoablation of the left atrium and pulmonary veins was performed. Our case describes the potential benefit of preoperative noninvasive mapping for the development of a surgical ablation strategy, as well as the challenges in managing urgent surgical patients during the COVID-19 pandemic and the corresponding diagnostic relevance of CT.